The Nano Curcumin - The Little One with The Big Impact : A Review - Tanfil. T, Ardy; Setiadi, Feri; Ridhayanah, Muthiah (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2022)
Curcumin is a compound contained in Curcuma longa, and this compound has many health benefits. One of the problems of this compound is its poor bioavailability, but methods to solve this problem have been found. One way to overcome the problem of curcumin bioavailability is to make curcumin in nano dosage forms. This article discusses the potential of curcumin nano as a future therapy for various diseases. We take a variety of sources by considering the source based on the index owned by the source. Scopus, Web of Science and Sinta are our main parameters. Articles not indexed by all three indexers are included in our rating. In conclusion, we found that curcumin in nano form has a very good potential to be used as a future therapy. However, further research is still needed to see the side effects of nano curcumin if used in the long term